1994
DOI: 10.1002/ange.19941061107
|View full text |Cite
|
Sign up to set email alerts
|

Tetraoxa[22]porphyrin(2.2.2.2)‐Dikation und Tetraoxa[24]porphyrinogen(2.2.2.2)

Abstract: Neben den Porphyrin-Homologen ([22]Porphyrin(2.2.2.2)['], [26]P0rphyrin(3.3.3.3)[~]) und den Porphyrin-Analoga ([18]Porphyrin(2.0.2.0)131, [22]P0rphyrin(l.3.1.3)'~]) gehoren die von E. Vogel et al. erschlossenen dikationischen [18]Porphyrinoide-(1.1.1.1) 1 zu den faszinierendsten neuen Entwicklungen in der Porphyrinchemie der letzten Jahre. Formal analog zu den N,N',N",N"'-Tetrameth ylporphyrin-Dikationen Z['] beschrie-R (3 2, X = N M e R x x \ \ ' / R ben 1988 E. Vogel et aLL6] erstmals das Tetraoxa[lS]porphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
6

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 25 publications
0
3
0
6
Order By: Relevance
“…A thermolysis study showed that 6 rearranges in boiling o-xylene (24 h) to form irreversibly the sterically uniform cis,trans,cis,trans isomer 7 (black-green crystals from ethyl acetate; decomposition above 300 8C; yield 65 %). [10] While our investigations on tetraoxa [22]porphyrin-(2.2.2.2) dications were still in progress, [10] Märkl et al [11] reported an independent synthesis of 7 and its successful oxidation to the dication 8. Since the results of the two groups are in satisfactory agreement mention is made to reference [10] regarding the physical data of 7 and 8 determined here.…”
mentioning
confidence: 99%
“…A thermolysis study showed that 6 rearranges in boiling o-xylene (24 h) to form irreversibly the sterically uniform cis,trans,cis,trans isomer 7 (black-green crystals from ethyl acetate; decomposition above 300 8C; yield 65 %). [10] While our investigations on tetraoxa [22]porphyrin-(2.2.2.2) dications were still in progress, [10] Märkl et al [11] reported an independent synthesis of 7 and its successful oxidation to the dication 8. Since the results of the two groups are in satisfactory agreement mention is made to reference [10] regarding the physical data of 7 and 8 determined here.…”
mentioning
confidence: 99%
“…So konnten wir zeigen, dass in den paratropen, antiaromatischen Annulenen, dem (Z,E,E,Z)-Tetraepoxy [3]. Im ebenfalls aromatischen (Z,E,Z,E,Z)-Diepoxy[18]annulen(10.0) [7] wie im antiaromatischen (Z,Z,E,Z)-Diepoxy [16]annulen(6.2) [8] rotieren die (E)-Ethen-1,2-diyl-Brückenglieder in der 1,3,5,7, 2) 4b. Im Gegensatz zum 1 H-NMRSpektrum von 4a mit den d-Werten für die Protonen in den rotierenden (E,E)-Buta-1,3-dien-1,4-diyl-und (E)-Ethen-1,2-diyl-Brücken bei 6 ppm weist das 1 H-NMRSpektrum von 4b keine Signale in diesem Bereich auf (Fig.…”
unclassified
“…Eine Thermolysestudie ergab, dass sich 6 in siedendem o-Xylol (24 h) irreversibel in das sterisch einheitliche cis,trans,cis,trans-Isomer 7 umlagert (schwarzgrüne Kristalle aus Essigester; Zersetzung b 300 8C; Ausbeute 65 %). [10] Während unsere Untersuchungen über Tetraoxa [22]porphyrin-(2.2.2.2)-Dikationen noch im Gang waren, [10] berichteten Märkl et al [11] über eine unabhängige Synthese von 7 und dessen erfolgreiche Oxidation zum Dikation 8. Da die Ergebnisse beider Arbeitskreise zufriedenstellend übereinstimmen, sei bezüglich der hier ermittelten physikalischen Daten von 7 und 8 auf Lit.…”
Section: Professor Dieter Seebach Gewidmetunclassified